FACTORS THAT INFLUENCE THE FARMERS’ SELECTION IN CROPPING PATTERNS FOR INTERCROPPING-COCOA FARMING AT KOLAKA REGENCY - Kabul Budiman (Agribusiness Journal, 2016)
Selection of the cropping pattern is a way of farmer in managing their resources. Various reasons were expressed by farmers related to the characteristic of a type of plant suitable to the farmers’ expectation. The purpose of the research was to know the factors that influence the selection of farmers in cropping patterns. Multiple cropping is double planting system which is an effort to get the crops more than once from a single type or multiple types of crops on the same plot of land for one year. The analysis used was multinomial logit analysis. Positive factors that influence the selection of farmers in cropping patterns in intercropping cocoa farming were: the number of family members, guidance from agriculture instructors, age of farmers, farmer’s experience, the success of other farmers and land positions.  Meanwhile, land size variable did not give effect on the selection of KKJ (cacao-coconut cashewnut pattern) and KKP (cacao-coconut-banana pattern) upon KKN (cacao-coconut-patchouli pattern).  It could be seen from the comparison of the coefficient (β) which was greater than the value of the probability.